Pengaruh Penambahan Zat Epoxy Resin dan Polypropylene Fiber Mesh (PFM) Terhadap Kuat Lentur Beton - Samuel Huaso Hatongamon Sianturi; Lolom Evalita Hutabarat; Setiyadi (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
Polypropylene fiber is made from chemical hydrocarbon compounds (C3H6) in single filaments or thin fibrous networks. Because the plastic fibers of polypropylene fiber mesh function as anti-cracking and reduce the brittle properties of concrete, a mixture of PFM and epoxy resin can increase the compressive strength and flexibility of concrete referred to ACI Committee 544. The polypropylene fiber additions used in this study were 0.60 kg/m3, 0.70 kg/m3, and 0.80 kg/m3, with an addition of 8% epoxy resin. Sixteen blocks (15 cm x 15 cm x 60 cm) with a design compressive strength of f'c 25MPa and a water-cement factor of 0.61. SNI 7656-2012 is referred to in the test standard. Compression and flexure tests were performed at 14 and 28 days of age. With the addition of 0.7 kg/m3 polypropylene fiber mesh, the compressive strength increased by 9.56% at 14 days of concrete age to 27.39 MPa. Meanwhile, at 28 days, it had risen by 20% or 30 MPa. Furthermore, for 14 days, the bending moment was 11943766.2 N.mm, and for 28 days, it was 13246692.5 N.mm.